Effects of Asphalt Source, Asphalt Grade, and Inclusion of Additives on Asphalt Foaming Characteristics. Issue 1 (January 2015) - Zhang, Jun; Arambula, Edith; Newcomb, David; Bhasin, Amit; Little, Dallas
Warm-mix asphalt (WMA) produced by foaming is widely used in the asphalt paving industry and is the largest segment of the WMA market in the United States. To produce foaming, a small quantity of cold water is injected into hot asphalt to cause a reduction in the asphalt viscosity and improve the coating of the aggregate particles. The primary objectives of the study reported here were to compare the foaming characteristics of asphalts of different sources and grades and to evaluate the effect of certain additives on the characteristics of the foamed asphalt. To characterize the foamed asphalt, a laser distance meter (LDM) was used in the laboratory. The LDM was used as an alternative to the dipstick (traditionally used in foaming measurements) because of its better repeatability and accuracy. The LDM results indicated that the foaming characteristics depended on the source and performance grade of the asphalt. The addition of a foaming-enhancing additive had a significant effect on the foaming characteristics of most asphalt. However, no obvious difference in foaming characteristics was observed when warm-mix additives were used as part of the foaming process.